Transformation of Teachers’ Work Culture through the Principal’s Managerial Leadership - Efra Risanti; Manap Somantri; Muhammad Kristiawan (Journal of Social Work and Science Education, 2026)
Principals in resource-limited primary schools face unique challenges in fostering a positive work culture among teachers. This study explores the managerial strategies of the principal at State Elementary School 44 South Bengkulu in enhancing teachers’ discipline, motivation, collaboration, and responsibility. Using a qualitative case study approach, data were collected through observation, interviews, and document analysis, and processed with data reduction, presentation, and verification techniques. Findings show that the principal employed structured strategies of planning, monitoring, evaluation, and follow-up, while addressing challenges such as limited facilities, administrative burdens, bureaucratic demands, and varying levels of teacher motivation. The study concludes that adaptive and communicative leadership is crucial in transforming teachers’ work culture, and it offers practical insights into flexible policy support, reward systems, and managerial leadership training for similar educational contexts.